Temperature and Salt Responsivity of Anionic, Cationic and Amphoteric Nanogels Based on N-Isopropylacrylamide, 2-Acrylamido-2-Methyl-1-Propanesulfonic Acid Sodium Salt and (3-Acrylamidopropyl) Trimethylammonium Chloride - Ayazbayeva, A.Ye.; Shakhvorostov, A.V.; Kudaibergenov, S.E. (Karagandy University of the name of academician E.A. Buketov, 2022)
Three different nanogels possessing anionic, cationic and amphoteric character were synthesized via conventional redox initiated free radical copolymerization of N-isopropylacrylamide (NIPAM), 2-acrylamido-2- methyl-1-propanesulfonic acid sodium salt (AMPS) and (3-acrylamidopropyl) trimethylammonium chloride (APTAC). The negatively charged [NIPAM]:[AMPS] = 90:10 mol.%, positively charged [NIPAM]:[APTAC] = = 90:10 mol.%, and charge-balanced amphoteric nanogels [NIPAM]:[APTAC]:[AMPS] = 90:5:5 mol.% abbreviated as NIPAM90-AMPS10, NIPAM90-APTAC10, and NIPAM90-APTAC5-AMPS5, respectively, were characterized by FTIR spectroscopy, TGA, UV-Vis spectroscopy and DLS measurements. The temperature and salt responsive properties of nanogels in aqueous and aqueous-salt solutions were studied in the temperature range of 25–60 °C and ionic strength (μ) of 0.001–1.0 M NaCl. Anionic NIPAM90-AMPS10 and cationic NIPAM90-APTAC10 nanogels, exhibit a pronounced polyelectrolyte effect in aqueous-salt solution due to screening of the negative or positive charges by low-molecular-weight salt. Whereas the charge-balanced amphoteric nanogel NIPAM90-APTAC5-AMPS5 exhibits an antipolyelectrolyte effect due to the screening of electrostatic attraction between opposite charges by low-molecular-weight salt. The difference between the temperature-dependent behaviors of anionic, cationic and amphoteric nanogels is explained by shrinking (polyelectrolyte effect) and expanding (antipolyelectrolyte effect) of macromolecular chains in aqueous-salt solutions.
N-изопропилакриламид, 2-акриламидо-2-метил-1-пропансульфон қышқылы натрий тұзы және (3-акриламидопропил)триметиламмоний хлориді негізіндегі анионды, катионды және амфотерлі наногельдердің температураға және тұзға сезімталдығы
Температурная и солевая чувствительность анионного, катионного и амфотерного наногелей на основе N-изопропилакриламида, натриевой соли 2-акриламидо-2-метил-1-пропансульфоновой кислоты и (3-акриламидопропил)триметиламмоний хлорида
Keywords: polyampholyte nanogels; poly-N-isopropylacrylamide; ionic monomers; volume phase transition temperature; amphoteric nanogel; anionic nanogel; cationic nanogel